Indonesian young consumers’ intention to donate using sharia fintech - Maulida Dwi Agustiningsih; Ravika Mutiara Savitrah; Putri Catur Ayu Lestari (Faculty of Business & Economics, Universitas Islam Indonesia, 2021)
Purpose: This research examines the effect of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), religiosity, and company image on intention to use Sharia fintech for donation among Indonesian young consumers.Methodology: This study used a quantitative method with data collection techniques using an online questionnaire. Respondents filled out the questionnaire based on the Likert scale from 1 (strongly disagree) to 4 (strongly agree). The questionnaire was distributed and collected in less than one week, from 26th March 2021 to 29th March 2021. The ideal sample is five times higher than the number of indicators. The number of indicators is 20, so the ideal sample is 100 or more. This study has successfully collected 206 respondents. However, 13 respondents filled the same scale for all questions, so 193 is chosen as data analysis. The valid data were analyzed through Structural Equation Modeling Partial Least Square (SEM-PLS). Findings: This research shows the intention to use Sharia fintech to pay donations influenced by perceived usefulness (PU) and religiosity. In contrast, perceived ease of use (PEOU) and image are not positively related to the intention of using Sharia fintech for donation.Practical Implication: Religiosity and PU positively influence the interest in using Sharia fintech to pay donation. So, it is expected for fintech to comply with Sharia compliance and still comply with regulations from the OJK and DSN related to legality aspects. Furthermore, fintech startups and developers can build a more user-friendly application.Originality: This research is a replication-based model and is adapted from published research. The originality in this research is in the respondent who young generation. Intention to pay donation using fintech Sharia is the main focus to be researched. This primary focus has not been being researched beforehand.